Sertifikasi Halal Badan Penyelenggara Jaminan Produk Halal (BPJPH) dalam Perspektif Yuridis - Chulsum Layyinatul Chasanah; Shofiyullah Muzammil (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Halal Product Guarantee Administering Body (BPJPH) is an official institution that has been authorized based on the mandate of Law no. 30 of 2014 concerning Halal Product Guarantees. BPJPH has high authority in implementing halal certification. Halal certification is mandatory for halal business actors in Indonesia. This research aims to find out how the halal certification process is carried out by BPJPH and the reasons behind why BPJPH implements regulations like this. The research method used is qualitative with a juridical or normative legal approach. This research is included in library research or library research by reviewing literature that is appropriate to the research object. The data sources used are the Halal Product Guarantee Law (UU JPH) and its derivatives and the official BPJPH account which is normative and can be accessed by the public. The research results show that halal certification by BPJPH is carried out in two ways, namely independently/regularly and self-declare. Each has a different halal certification flow. The legal basis for implementing halal certification by BPJPH is Law no. 30 of 2014 concerning Halal Product Guarantees, Government Regulation Number 31 of 2019 concerning Implementation of Halal Product Guarantees, Minister of Religion Regulation Number 26 of 2019 concerning Procedures for Halal Certification, and BPJPH Regulation Number 61 of 2022 concerning SOPs for Halal Certificate Application Services at BPJPH.